The neural correlates of Childhood Trauma Questionnaire scores in adults: A meta-analysis and review of functional magnetic resonance imaging studies. (11th December 2017) - Heany, Sarah J.; Groenewold, Nynke A.; Uhlmann, Anne; Dalvie, Shareefa; Stein, Dan J.; Brooks, Samantha J.
Abstract: Childhood maltreatment, including abuse and neglect, may have sustained effects on the integrity and functioning of the brain, alter neurophysiological responsivity later in life, and predispose individuals toward psychiatric conditions involving socioaffective disturbances. This meta-analysis aims to quantify associations between self-reported childhood maltreatment and brain function in response to socioaffective cues in adults. Seventeen functional magnetic resonance imaging studies reporting on data from 848 individuals examined with the Childhood Trauma Questionnaire were included in a meta-analysis of whole-brain findings, or a review of region of interest findings. The spatial consistency of peak activations associated with maltreatment exposure was tested using activation likelihood estimation, using a threshold of p < .05 corrected for multiple comparisons. Adults exposed to childhood maltreatment showed significantly increased activation in the left superior frontal gyrus and left middle temporal gyrus, and decreased activation in the left superior parietal lobule and the left hippocampus. Although hyperresponsivity to socioaffective cues in the amygdala and ventral anterior cingulate cortex in correlation with maltreatment severity is a replicated finding in region of interest studies, null results are reported as well. The findings suggest that childhood maltreatment has sustained effects on brain function into adulthood, and highlight potential mechanisms for conveying vulnerability to development of psychopathology.